Development of algorithm for different programmable modes for a prototype of orthotic ambulatory device for gait rehabilitation. (2017) - Dutta, Ritushree; Kumar, Neelesh; Bora, Dhruba Jyoti
Presently available orthotic devices have many limitations in their mechanical design, sensor mechanism and real-time control to achieve stable, efficient and human like bipedal walking. User adaptive control algorithm with different programmable modes for developed prototype of an orthotic device is implemented. Gait postures like sit, stand, walk, stair walk, user defined exercise mode, etc., are basic human mobility functions. These activities are part of rehabilitation therapy for a locomotive disabled. With emerging trend of robotic rehabilitation, orthotic devices with good control strategy that helps in early recovery and more effective in gait rehabilitation are required. Control strategy is based on gait parameters like lower limb joint angles and ground reaction force. Software algorithm is developed in LabVIEW platform for different modes like sit, stand, walk and stair climbing. Implemented control strategy is verified based on the trajectory error estimated of hip, knee and ankle of the device are analysed. These trajectories are compared with the standard available data.